The complete encyclopedia of tractors - De Cet, Mirco (Rebo International, 2006)
This book traces the intriguing histories of all the major tractor manufactures--John Deere, Massey-Ferguson, New Holland to name a few--as well as those of smaller, but nevertheless important producers. The pioneer companies--the likes of Hart Parr, Ivel and Lanz--who have either disappeared entirely, or who were swallowed up by the larger concerns. From the earliest steam traction engines to the latest hi-tech, computerized machines of today, "The Complete Encyclopedia of Tractors" follows the trials and tribulations of men and their inventions through the Depression, wars and famine, to develop agricultural machinery that would help keep the world's population fed.-- From the publisher.